2017
DOI: 10.1007/s00330-017-4911-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of cone-beam breast-CT for breast cancer detection relative to breast density

Abstract: • Overall sensitivity for non-contrast CBBCT ranged between 88%-91%. • Sensitivity was higher for CBBCT than mammography in both density types (p<0.001). • Specificity was higher for mammography than CBBCT in both density types (p<0.05). • AUC was larger for mammography than CBBCT in both density types (p<0.001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 28 publications
3
45
0
1
Order By: Relevance
“…Breast computed tomography is a cross-sectional imaging technique with a proven higher diagnostic accuracy compared with mammography regarding breast lesions. [11][12][13] The higher accuracy results from the largely resolved overlapping of the breast tissue and the possibility to analyze imaging findings in multiple anatomical planes from a single scan. Up to now, resolution of B-CT did not reach high enough resolution to visualize microcalcifications, which the new dedicated B-CT can provide.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Breast computed tomography is a cross-sectional imaging technique with a proven higher diagnostic accuracy compared with mammography regarding breast lesions. [11][12][13] The higher accuracy results from the largely resolved overlapping of the breast tissue and the possibility to analyze imaging findings in multiple anatomical planes from a single scan. Up to now, resolution of B-CT did not reach high enough resolution to visualize microcalcifications, which the new dedicated B-CT can provide.…”
Section: Discussionmentioning
confidence: 99%
“…Breast computed tomography has the potential to further improve breast lesion detection and characterization compared with mammography and tomosynthesis. [11][12][13] Previous studies investigating the use of cone beam B-CT in comparison to mammography reported higher radiation doses for B-CT, especially when referring to a screening setting. 13,14 More recently, new strategies have strongly increased the dose efficiency due to the use of novel photon-counting detector technology, resulting in dose levels for B-CT comparable to those of screening mammography or lower.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CTDIw = 8 mGy ± 20% with one 360°scan at 49 kVp, 100 mA, and 8 ms pulse duration) [9]. Reports indicate that in BCT exams the MGD can be comparable to that of diagnostic mammography [9,10,55], and several times larger than that used in two-view screening mammography [28,56]. Sechopoulos et al [28] calculated the pDgN CT coefficients for the Koning Corp. scanner located at the Emory University (whose scans are adopted in this work, with beam quality 49 kVp and HVL = 1.39 mm Al).…”
Section: Discussionmentioning
confidence: 99%
“…Dedicated Breast Computed Tomography (DBCT) uses a cone-beam system to perform a true tomographic scan capable of achieving near isotropic resolution in any plane with less noise than DBT and without breast compression [89], and has been demonstrated to be 21.5% more sensitive than mammography in detecting breast lesions [125]. Still in the innovation stages, current prototypes position the patient prone over a breast aperture enabling exclusion of the thorax and body from radiation exposure.…”
Section: Approaches Which Employ Ionising Radiationmentioning
confidence: 99%